2011
DOI: 10.1007/s10518-011-9244-8
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of air temperature on the cyclic behavior of elastomeric seismic isolators

Abstract: Themechanical properties of elastomers can change significantly due to air temperature variations. In particular, prolonged exposure to subzero temperatures can result in rubber crystallization, with a considerable increase in the shear stiffness of the material. As a result, the seismic response of structures with elastomeric isolators can be strongly influenced by air temperature. Current seismic codes, indeed, require an upper and lower bound analysis, using suitable modification factors, to account for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…These stress-softening behaviors seem to result from the healing of Mullins effect [20,21] occurring with the time lapse between finish of the preloading and start of the actual test. However, the temperature rise inside HDRBs is remarkable at low temperatures [8,36]. This rise also may cause some effect on stress responses in the 1st cycle of CS tests.…”
Section: Cyclic Loading Tests With Constant Strain Rate (Cs) and Varimentioning
confidence: 99%
See 2 more Smart Citations
“…These stress-softening behaviors seem to result from the healing of Mullins effect [20,21] occurring with the time lapse between finish of the preloading and start of the actual test. However, the temperature rise inside HDRBs is remarkable at low temperatures [8,36]. This rise also may cause some effect on stress responses in the 1st cycle of CS tests.…”
Section: Cyclic Loading Tests With Constant Strain Rate (Cs) and Varimentioning
confidence: 99%
“…In order to minimize the self-heating effect [8,32] on the overstress parameter identification, the 1st cycle shear stressstrain response of sinusoidal loading tests are used in the parameter identification procedure. This assures achieving a thermal boundary condition compatible with the formulation.…”
Section: Scheme To Identify Optimal Overstress Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of scientific and technical sources [16,19,23] note dependence of horizontal stiffness and damping ratio on temperature and vibration frequency. The standard [4] also noted the behavior features of isolation bearings under vertical load such as creep and bedding.…”
Section: Studying Of Elastomeric Isolators Behaviourmentioning
confidence: 99%
“…Test results showed that low-temperature shear stiffness of the test bearings was almost twice as much as their room temperature stiffness. In two recently published papers [8,9], an experimental study to investigate the sensitivity of the cyclic behavior of elastomeric materials to air temperature variations on six different types of elastomers, characterized by a shear modulus ranging from 0.5 to 1.2 MPa at 100 % shear strain and 20 • C, are carried out. The cyclic tests have been performed at seven different air temperatures ranging from 40 to −20 • C. The effects of rubber crystallization due to prolonged exposure to low temperatures have been also investigated.…”
Section: Introductionmentioning
confidence: 99%